Summary Proceedings of the Fifty-Fifth Annual Meeting of the Board of Governors, September 26-28, 2000. (Summary Proceedings; 55th Annual Meeting 2000, 2000)
The speeches made by officials attending the IMF-World Bank Annual Meetings are published in this volume, along with the press communiques issued by the International Monetary and Financial Committee and the Development Committee at the conclusion of the meetings.